FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN KONSUMEN PRIMER - Destiayu , Silvia Elsa; Surjadi, Lukman (Jurnal Paradigma Akuntansi, 2025)
This study aims to obtain empirical evidence regarding the effect of profitability, liquidity, tangibility, sales growth, and company size on the capital structure in primary consumer sector companies listed on the Indonesia Stock Exchange (IDX) in the 2019–2021 period. The sample used in this study was 35 companies in the primary consumer sector, which were selected based on the purposive sampling method. Data collected with the help of Microsoft Excel 2013 software, and processed using Eviews 12 software shows that in this study profitability (ROA), liquidity (CR) and tangibility (FAR) have a negative effect on capital structure (DER). Meanwhile, capital structure (DER) is unaffected by sales growth (GROWTH) or company size (SIZE). The implication of this study is that managers can pay attention to what factors affect the capital structure because an optimal capital structure can attract the attention of investors.